Development and evaluation of Intelligent Risk Assessment and Early Warning System for deterioration in pediatric patients - Zhang, Yingying (My University, 2022)
Objective To develop ‘intelligent Risk Assessment and Early Warning System of pediatric deterioration’ (iRA-EWS) to improve nurses’ performance of using Pediatric Early Warning Score (PEWS). Methods A semi-structured interview was conducted to describe nurses’ experience of using PEWS and requirements about functions of iRA-EWS. Meanwhile, functions of electronic PEWS assessment system (e-PEWS) and currently used response strategy after PEWS assessment were sort out. The above two steps were used as a baseline, combined with Clinical Decision Support System-Reference Model (CDSS-RM) as framework to form preliminary function scheme of iRA-EWS and to specify currently used response strategy. Then consensus of clinical experts was used to discuss the feasibility of preliminary function scheme of iRA-EWS and specified response strategy to form function scheme of iRA-EWS. And function scheme of iRA-EWS was submitted to engineers for development. A before and after controlled trial was used to evaluate effectiveness of iRA-EWS in improving nurses’ performance of using of PEWS and a mixed study was used to describe nurses’ experience of using iRA-EWS. Results Lacking a risk warning function, wrong records, lacking awareness of dynamic assessment, simplistic response strategy, incomplete documentation of adopted strategies after assessment, lack of statistical view, and lack of data sharing were problems under e-PEWS. Clinical nurses’ requirements about functions of iRA-EWS were assessment support and decision support. Based on the problems encountered and clinical nurses’ needs, combined with CDSS-RM as framework, iRA-EWS was developed with the functions of color codes, assessment triggering, strategy recommendation and clear statistical display. iRA-EWS increased correctness of PEWS record from 78.99% to 89.02% (P<0.001). In improving the timeliness of PEWS assessment at the three time points of admission, first aid, and transportation, there was no significant difference between before and after the use of iRA-EWS (P>0.05). But iRA-EWS can significantly improve the timeliness of PEWS assessment when consciousness was abnormal, or oxygen intake was abnormal, from 46.64% to 100% (P<0.001). After the application of iRA-EWS, completeness of PEWS related nursing procedure records was increased from 46.64% to 100% (P<0.001). Nurses generally had a good experience in use of iRA-EWS. Conclusions iRA-EWS, which is guided by clinical problems, combined with the needs of clinical nurses, and based on the theoretical model of CDSS-RM, is professional, scientific, and practical. It improves correctness of PEWS records, timeliness of PEWS assessment and integrity of PEWS related nursing procedure records. Nurses generally have a good experience in usage of iRA-EWS and consider that it could be further optimized.
Keywords: Pediatric early warning score, Deterioration, Nursing information system, Clinical decision support system